1997
DOI: 10.1093/jn/127.9.1795
|View full text |Cite
|
Sign up to set email alerts
|

Phytoestrogens Reduce Bone Loss and Bone Resorption in Oophorectomized Rats

Abstract: To examine a potential role for phytoestrogens in postmenopausal bone loss, the oophorectomized (OOX) rat model has been used in three studies to investigate the effects of the phytoestrogens coumestrol, zearalanol and a mixture of isoflavones on estrogen-dependent bone loss. In the studies of coumestrol and zearalanol, the rats were allocated to a control group, a phytoestrogen-treated group (1.5 micromol coumestrol or 3.1 mmol zearalanol twice per week, intramuscular) or, in the coumestrol study, an estrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
0
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(61 citation statements)
references
References 18 publications
0
59
0
2
Order By: Relevance
“…Much higher oral doses (50-400 mg/kg/day) of IPR have been required to prevent bone loss in ovariectomized rats (138), doses that also produce plasma concentrations similar to the effective in vitro concentrations (139,140). COM also inhibits bone resorption in vitro (141) and is a more potent agent, preventing bone loss at oral doses of 1-2 mg/kg/day (142,143). Results with GEN, on the other hand, have been inconsistent.…”
Section: Bone Densitymentioning
confidence: 99%
“…Much higher oral doses (50-400 mg/kg/day) of IPR have been required to prevent bone loss in ovariectomized rats (138), doses that also produce plasma concentrations similar to the effective in vitro concentrations (139,140). COM also inhibits bone resorption in vitro (141) and is a more potent agent, preventing bone loss at oral doses of 1-2 mg/kg/day (142,143). Results with GEN, on the other hand, have been inconsistent.…”
Section: Bone Densitymentioning
confidence: 99%
“…Phytoestrogens were also found to participate in other events, e.g. cancer development [12], prevention of osteoporosis [2,3], corticosteroid synthesis disturbances, reduction of cardiovascular diseases [2], and the protection of LDL against oxidative modifications [11,14] [1]. One of the effects is the reduction of the inhibitory action of insulin on lipolysis [1].…”
mentioning
confidence: 99%
“…This is supported by the observation that certain phytoestrogens, such as genistein, coumestrol, or zearalenol, are able to bind to the estrogen receptors and modulate a variety of estrogendependent processes (Stahl et al, 1998). Furthermore it has been suggested that ␣-zearalenol shows interesting bioactivity in preventing bone loss in a wellrecognized model of postmenopausal osteoporosis in the rat (Draper et al, 1997).…”
Section: Discussionmentioning
confidence: 90%
“…The treatment lasted 4 weeks. The doses of 17␤-estradiol and ␣-zearalenol were selected according to previous studies of the effects of both compounds in OVX rats (Draper et al, 1997;Squadrito et al, 1996). It has been suggested that the estrogenic potency of ␣-zearalenol relative to 17␤-estradiol is 50 times less (Everett et al, 1987).…”
Section: Estrogen and ␣-Zearalenol Supplementationmentioning
confidence: 99%
See 1 more Smart Citation